2004
DOI: 10.1177/0091270004267590
|View full text |Cite
|
Sign up to set email alerts
|

Central Effects of Fexofenadine and Cetirizine: Measurement of Psychomotor Performance, Subjective Sleepiness, and Brain Histamine H1‐Receptor Occupancy Using 11C‐Doxepin Positron Emission Tomography

Abstract: Histamine H1-receptor (H1R) antagonists, or antihistamines, often induce sedative side effects when used for the treatment of allergic disorders. This study compared the sedative profiles of the second-generation antihistamines, fexofenadine and cetirizine, using 3 different criteria: subjective sleepiness evaluated by the Stanford Sleepiness Scale, objective psychomotor tests (simple and choice reaction time tests and visual discrimination tests at 4 different exposure durations), and measurement of histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 48 publications
3
115
1
4
Order By: Relevance
“…46,[49][50][51][52] The significant sedation associated with first-generation and certain secondgeneration antihistamines is attributed to their high liposolubility and low molecular weight -which allows penetration into the CNS -and their high affinity for CNS histamine H 1 receptors. 42,[49][50][51][52][53] Most newer second-generation antihistamines have minimal or no sedating properties (due to minimal CNS penetration and a low affinity for central H 1 receptors) and less anticholinergic effects and are therefore preferable to first-generation antihistamines in most cases. [46][47][48][49] The second-generation antihistamine, cetirizine, however, does penetrate the CNS and occupy central H 1 receptors to some extent, resulting in increased sedation compared with fexofenadine.…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…46,[49][50][51][52] The significant sedation associated with first-generation and certain secondgeneration antihistamines is attributed to their high liposolubility and low molecular weight -which allows penetration into the CNS -and their high affinity for CNS histamine H 1 receptors. 42,[49][50][51][52][53] Most newer second-generation antihistamines have minimal or no sedating properties (due to minimal CNS penetration and a low affinity for central H 1 receptors) and less anticholinergic effects and are therefore preferable to first-generation antihistamines in most cases. [46][47][48][49] The second-generation antihistamine, cetirizine, however, does penetrate the CNS and occupy central H 1 receptors to some extent, resulting in increased sedation compared with fexofenadine.…”
Section: 24mentioning
confidence: 99%
“…[46][47][48][49] The second-generation antihistamine, cetirizine, however, does penetrate the CNS and occupy central H 1 receptors to some extent, resulting in increased sedation compared with fexofenadine. 42,53,54 Azelastine, an intranasal antihistamine with anti-inflammatory properties, has reduced nasal congestion and improved subjective sleep quality in small studies, but was also found to cause somnolence. 55,56 Decongestants are sympathomimetic drugs that constrict capacitance vessels in the turbinates and decrease nasal congestion.…”
Section: 24mentioning
confidence: 99%
“…Для него характерны низкий потенциал к лекарственным взаимодействиям, отсутствие способности потенцировать влияние алкоголя на ЦНС и потребности в коррекции дозы при нарушениях функции почек и/или печени. Данные качества позволяют считать препарат Никсар ® одним из лидеров среди Н 1 -антигистаминных препаратов второго поколения [16].…”
Section: выводыunclassified
“…It also became apparent that antihistamines differ in their substrate specificity for P-glycoprotein, fexofenadine being a particularly good substrate[52]. In the brain, the H 1 -receptor occupancy of fexofenadine assessed using positron emission tomography scanning is negligible, <0.1%, and, in psychomotor tests, fexofenadine is not significantly different from placebo[53]. Furthermore, fexofenadine has been shown to be devoid of central nervous effects even at supraclinical doses, up to 360 mg[54].…”
Section: Second-generation H1-antihistaminesmentioning
confidence: 99%